(untitled) (Journal of Informatics Education and Research, 2025)
This project presents a comparative research on the strength characteristics of normal concrete and Sugarcrete—a sustainable construction material that incorporates using by ash from sugarcane fibers, to some percentage replace cement. The study aims to evaluate the mechanical performance, particularly compressive strength, of both materials under standardized conditions. Concrete samples were made by applying distinct amounts of SCBA in the sugarcrete mixture, and after 7, 14,28 days of healing, they were evaluated. The construction industry significantly contributes to global carbon emissions, primarily through the production of conventional Portland cement. In an effort to explore more sustainable building materials, this study investigates the comparative strength analysis of normal concrete and Sugarcrete. Sugarcrete is an innovative composite material that incorporates cement can be partially replaced by ash from sugarcane fibers, a byproduct of the sugar production mills . This research attempts to assess the mechanical capabilities of Sugarcrete, particularly focusing on compressive strength, and compare it with that of standard concrete.